Nano casein–pectin complex: exploring physicochemical, organoleptic properties, and LAB viability in skimmed milk and low-fat yoghurt - Gomaa, Mohamed A. E.; Allam, Marwa G.; Mokhtar, Esraa; Ayad, Eman H. E.; Darwish, Saeid M.; Darwish, Amira M. G. (Frontiers in Nutrition, 2024)
The protein complexes with nutritional value, heat stability and gelling properties with no negative impact on culture viability have promising application prospects in fermentation industry. The aim of work was to investigate the possibility of applying physical modification seeking high protein fortified yoghurt production using nano casein-pectin NCP complex as an active colloidal system with enhanced structural and thermal properties, and monitor the quality properties of; the physicochemical, heat stability, rheological, starter culture viability and sensory evaluation of fortified products comparing with the plain control throughout the cold storage. The particle sizes showed to be (≈166 nm and 602.6 nm) for nano-casein and pectin respectively. Milk fortification with NCP complex has significantly increased the nutritional value represented in; increased protein content (7.19 g/100g in NCP5), Ca, P and S content (2,193.11, 481.21 and 313.77 ppm), amino acids content with first limiting amino acids; histidine (0.89 mg/g), methionine (0.89 mg/g), and low content of hydrophobic amino acids (HAAs) that may be a cause aggregation. NPC fortification enhanced physicochemical properties announced in enhanced viscosity (62. mP.s in NCP5) and heat stability (up to 200 o C) compared with control skimmed milk (SM). NCP yoghurt fortification significantly increased protein content to (11 mg/100g in T5), enhanced viscosity to (48.44 mP.s in T3), decreased syneresis to (16% in T5), and enhanced LAB viability which was translated in preferable sensorial properties. Applying fortification with nanoparticles of casein-pectin (NCP) complex balanced the amino acids content, improved physicochemical, rheological, nutritional, sensorial properties and LAB viability, which can be recommended in further in functional food applications.